'Relief of oppression': An organizing principle for researchers' obligations to participants in observational studies in the developing world - Upshur Ross EG; Kimani Joshua; Bandewar Sunita VS; Lavery James V; Plummer Frances A; Singer Peter A (BMC, 2010)
Abstract Background A central question in the debate about exploitation in international research is whether investigators and sponsors from high-income countries (HIC) have obligations to address background conditions of injustice in the communities in which they conduct their research, beyond the healthcare and other research-related needs of participants, to aspects of their basic life circumstances. Discussion In this paper, we describe the Majengo sexually transmitted disease (STD) Cohort study, a long-term prospective, observational cohort of sex workers in Nairobi, Kenya. Despite important scientific contributions and a wide range of benefits to the women of the cohort, most of the women have remained in the sex trade during their long-standing participation in the cohort, prompting allegations of exploitation. The Majengo STD cohort case extends the debate about justice in international research ethics beyond clinical trials into long-term observational research. We sketch the basic features of a new approach to understanding and operationalizing obligations of observational researchers, which we call 'relief of oppression'. 'Relief of oppression' is an organizing principle, analogous to the principle of harm reduction that is now widely applied in public health practice. Relief of oppression aims to help observational researchers working in conditions of injustice and deprivation to clarify their ethical obligations to participants. It aims to bridge the gap between a narrow, transaction-oriented account of avoiding exploitation and a broad account emphasizing obligations of reparation for historic injustices. We propose that relief of oppression might focus researchers' consideration of benefits on those that have some relevance to background conditions of injustice, and so elevate the priority of these benefits, in relation to others that might be considered and negotiated with participants, according to the degree to which the participating communities are constrained in their realization of fundamental freedoms. Summary The over-arching aim of relief of oppression is that, within the range of benefits negotiated over time with the local communities and organizations, an increasing proportion reflects a shared interest in improving participants' fundamental freedoms. We describe how harm reduction serves as a useful analogy for how we envision relief of oppression functioning in international research.